2004
DOI: 10.1080/13638490410001711515
|View full text |Cite
|
Sign up to set email alerts
|

The ‘unified hypothesis’ of Geddeset al. is not supported by the data

Abstract: Inflicted head injury to the developing brain frequently results in serious disability. The pathogenesis of the neuraxial and ocular findings in infants believed to have suffered inflicted head injury remains the subject of considerable debate. Recent neuropathology studies of fatal cases of inflicted head injury and of a foetal/perinatal non-traumatic model have led to the proposal that there is a 'unified hypothesis', the essential feature of which is hypoxic brain swelling secondary to cervicomedullary inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 29 publications
(83 reference statements)
0
31
0
Order By: Relevance
“…5 Thus, in some infants with unexplained SDH a presumptive diagnosis of AHT might be incorrect. Although controversial, 6 this "unified hypothesis" quickly appeared in court, culminating in a judicial review of criminal prosecutions for AHT in the United Kingdom, where deficiencies in the hypothesis were acknowledged. 7,8 Several subsequent postmortem studies have found no association between hypoxia and SDH in infancy, [9][10][11] but other authors continue to suggest a strong association between SDH and hypoxia in the presence of additional factors.…”
Section: Resultsmentioning
confidence: 99%
“…5 Thus, in some infants with unexplained SDH a presumptive diagnosis of AHT might be incorrect. Although controversial, 6 this "unified hypothesis" quickly appeared in court, culminating in a judicial review of criminal prosecutions for AHT in the United Kingdom, where deficiencies in the hypothesis were acknowledged. 7,8 Several subsequent postmortem studies have found no association between hypoxia and SDH in infancy, [9][10][11] but other authors continue to suggest a strong association between SDH and hypoxia in the presence of additional factors.…”
Section: Resultsmentioning
confidence: 99%
“…44 The 2003 had macroscopic SDH. 30 My own experience is that if the dura is adequately sampled, dural and subdural membrane bleeding is frequent in association with macroscopic SDH. Again, careful prospective studies are needed.…”
Section: Support For the Geddes Hypothesismentioning
confidence: 99%
“…Such was the seduction of precise mechanistic thinking that even Albert Einstein, when confronted with the ambiguities of the quantum world, declared in frustration that 'I shall never believe that God plays dice with the world'. 2 Controversies surrounding the diagnoses of autism 3,4 and nonaccidental head injury 5,6 are two of many examples that suggest an analogous degree of uncertainty applies to the world of community paediatrics. Traditionally, paediatrics has enjoyed the certainty of biologically defined constructs of health and health care as exemplified by the detail tested in the Fellow of the Royal Australasian College of Physicians (FRACP) written exam.…”
Section: Community Paediatrics In the Marketplacementioning
confidence: 99%